EVALUASI DAMPAK ALIH FUNGSI LAHAN PERTANIAN KE NON PERTANIAN DI KECAMATAN GUNUNGPATI KOTA SEMARANG - Budianingrum, Danny Marliana; Fathurrochman, Fathurrochman; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Population growth and Semarang’s development which outspread into urban area cause increasing of land requirement in urban area. Gunungpati District, one of urban areas around Semarang, becomes the area of Semarang’s development. How the land conversion in Gunungpati District occurs is because city development outspreads into urban area as well assupported by some facilities such as education and settlements. Hence, many agricultural lands convert for nonagricultural activity in Gunungpati District. Land conversion, mainly agricultural land conversion, causes the change of social and economic condition as well as the change of livelihood or employment of population. The purposes of this research are to discover the impact of land conversion from agricultural land into developed land, to know the change of social and economic condition of community, and also to know the available employment opportunity after land conversion occurs in Gunungpati. The research approach used is qualitative approach and method used is matrix Leopold. Designed to determine the impact on the region's natural environment. So that can know the value impact of the conversion of agricultural land to non-agricultural in District Gunungpati Semarang. The result of this research shows that agricultural land conversion into developed land in Gunungpati District has positive effect towards social and economic condition of society and has negative effect towards natural environment surround. According to Leopold matrix, the positive effects has values 25 are good value shown by improving quality of life and increasing the varieties of livelihood or employment, whereas the negative effects has values -13 are bad value shown by decreasing the amount of agricultural land and damaging the sanitation or water infiltration in Gunungpati District. The agricultural land conversion is suggested to divert less productive agricultural land so that it would not damage ecological function of Gunungpati District as infiltration water area.